2016
DOI: 10.7554/elife.09394
|View full text |Cite
|
Sign up to set email alerts
|

MHC-compatible bone marrow stromal/stem cells trigger fibrosis by activating host T cells in a scleroderma mouse model

Abstract: Fibrosis of organs is observed in systemic autoimmune disease. Using a scleroderma mouse, we show that transplantation of MHC compatible, minor antigen mismatched bone marrow stromal/stem cells (BMSCs) play a role in the pathogenesis of fibrosis. Removal of donor BMSCs rescued mice from disease. Freshly isolated PDGFRα+ Sca-1+ BMSCs expressed MHC class II following transplantation and activated host T cells. A decrease in FOXP3+ CD25+ Treg population was observed. T cells proliferated and secreted IL-6 when st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 53 publications
3
54
0
Order By: Relevance
“…We chose this animal model because it is well recognized as an established model of cGVHD and because it reflects the inflammation and fibrosis in target organs of cGVHD [ 19 ]. We have published several studies on lacrimal gland cGVHD in humans [ 11 , 18 ] and mice [ 20 , 21 ] and have observed that the lacrimal gland pathology of this animal model is quite similar to that of humans [ 11 , 18 ]. Dry eye disease is a major problem for patients suffering from cGVHD after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…We chose this animal model because it is well recognized as an established model of cGVHD and because it reflects the inflammation and fibrosis in target organs of cGVHD [ 19 ]. We have published several studies on lacrimal gland cGVHD in humans [ 11 , 18 ] and mice [ 20 , 21 ] and have observed that the lacrimal gland pathology of this animal model is quite similar to that of humans [ 11 , 18 ]. Dry eye disease is a major problem for patients suffering from cGVHD after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Murine models have shown that interaction between T cells and antigen-presenting cells, including macrophages contributed to the pathogenesis of ocular GVHD [17]. Migrating donor mesenchymal stem cells interact with T cells, leading to production of IL-6, a reduction of regulatory T cells, and an increase in Th17 effector T cells similar to what is seen in autoimmune pathologic processes [25].…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…Several murine models of ocular GVHD have been studied previously [17,24,25]. In vitro analysis has shown that fibroblasts derived from GVHD-involved lacrimal glands have highly proliferative, invasive, and migratory characteristics [26].…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…In particular, the following were noted: 1) the structures of intestinal villi in the inhibitor-treated small and large intestines were retained, in contrast to those in their vehicle-treated counterparts; 2) the vehicletreated skin was thicker, had less fatty tissue, and had greater density of collagen bundles than the inhibitortreated skin; and 3) meibomian glands in the vehiclemedicated eyes were fewer and smaller than their inhibitor-medicated equivalents. Furthermore, systemic fibrosis is highly problematic in GVHD (27,28). Mallory's staining indicated that fibrosis elicited by GVHD was considerably repressed in organs from inhibitor-medicated allo-BMT recipients in contrast to those from their vehicle-medicated equivalents (Fig.…”
Section: Immunohistochemical Investigation Into Inflammatory Cell Infmentioning
confidence: 99%